THE STAGES OF FORMATION THE TRAJECTORY OF PROFESSIONAL DEVELOPMENT OF STUDENTS OF PEDAGOGICAL INSTITUTE - Inna A. Tenyunina (Высшее образование в России)
This article presents the results of scientific and practical research on the problem of professional formation and development of students during the period of training at pedagogical institute. The article suggests describes stages of formation the trajectory of professional development of future teachers. The analysis of practice of pedagogical colleges shows that the educational process is aimed at improving the professional competence of the future specialist, while the individual identity of professional formation and development of a student during the whole period of his training is not sufficiently taken into account. The author in the course of the research work has made an attempt to create an educational environment conducive to intensification of personal, creative and professional potential of the student. Elucidation of the problems connected with the professional formation and development of students will give impetus to further research in the area of professional preparation of future teachers.